A Fat-Facets-Dscam1-JNK Pathway Enhances Axonal Growth in Development and after Injury - Koch, Marta; Nicolas, Maya; Zschaetzsch, Marlen; de Geest, Natalie; Claeys, Annelies; Yan, Jiekun; Morgan, Matthew J.; Erfurth, Maria-Luise; Holt, Matthew; Schmucker, Dietmar; Hassan, Bassem A. (Frontiers in Cellular Neuroscience, 2018)
Injury to the adult central nervous systems (CNS) can result in severe long-term disability because damaged CNS connections fail to regenerate after trauma. Identification of regulators that enhance the intrinsic growth capacity of severed axons is a first step to restore function. Here, we conducted a gain of function genetic screen in Drosophila to identify strong inducers of axonal growth after injury. We focus on a novel axis the Down Syndrome Cell Adhesion Molecule (Dscam1), the de-ubiquitinating enzyme Fat Facets (Faf)/Usp9x and the Jun N-Terminal Kinase (JNK) pathway transcription factor Kayak (Kay)/Fos. Genetic and biochemical analyses link these genes in a common signaling pathway whereby Faf stabilizes Dscam1 protein levels, by acting on the 3’-UTR of its mRNA, and Dscam1 acts upstream of the growth-promoting JNK signal. The mammalian homolog of Faf, Usp9x/FAM, shares both the regenerative and Dscam1 stabilizing activities, suggesting a conserved mechanism.